Administrative support functions in the era of prophecy: a study through the book Graduation of auditory semantics by Al-Khuzaie - Almusafri, Afra; AL-Leheabi, Saleh (Al-Adab Journal, 2024)
This study is limited to Medina and the regions of the State of Islam in the era of prophecy, and the importance of the study lies in highlighting the importance of the book "Graduation of auditory indications on what was in the era of the Messenger of God of crafts, crafts and legal labors", and to identify the personality of the writer, Ali Al-Khuzaie, and to see the opinions of scholars in it, and to identify the supporting administrative conditions in the era of prophecy, and to identify the administrative development of the judiciary institution, and to identify the security conditions that were in the era of prophecy.This study aims to introduce the development of administrative conditions in the era of prophecy, and to introduce Al-Khuza'i, the author of the book on which it was based in the study, and then to clarify the most prominent and important developments in administrative work in the era of prophecy, as well as supporting functions, without going into all the administrative references contained in the book to avoid prolongation and drowning in details.The research has been divided into two sections in the first section talks about Al-Khuzaie and the importance of writing, and the second section dealt with the administrative functions that were in the era of prophecy and these topics are the owner of the secret and the eyebrow and the book and the governor of the market.I have concluded many things and information that I did not know about, and it never occurred to me to look for them, and I have proven that Al-Khuzaie's book is really valuable, because of its many and comprehensive information on many topics.